Reliability of biological maturation analyses performed by equations predicting skeletal age and peak height velocity with hand and wrist X‐ray results. Issue 9 (25th June 2022) - de Almeida‐Neto, Paulo Francisco; de Medeiros, Jason Azevedo; Medeiros, Radamés Maciel Vítor; Baxter‐Jones, Adam; de Matos, Dihogo Gama; Aidar, Felipe J.; Dantas, Paulo Moreira Silva; de Araújo Tinoco Cabral, Breno Guilherme
Abstract: Background: Hand‐wrist radiography is the gold standard for the assessment of skeletal age (SA) and the assignment of biological maturation (BM) status. However, its practical use in the field is questioned, prompting the development of anthropometric equations to estimate BM. However, there is no consensus on the reliability of these equations in relation to hand‐wrist X‐rays. Objective: To test the reliability of the BM estimated from predictive equations with the results of hand‐wrist X‐rays. Methods: One‐hundred forty‐four young athletes (38%‐males, 62%‐females; 12.3 ± 1.4 years) were recruited. SA was assessed by analyzing X‐rays of the hand‐wrist using the Greulich‐Pyle protocol. SA was predicted using the anthropometric equations of Cabral and Macêdo. By subtracting chronological age from SA, a measure of BM or biological age (BA) was computed. In addition, a BA of years from peak height velocity (PHV) was predicted using the anthropometric equations of Mirwald and Moore. Results: Relative to X‐ray, Cabral's equations showed high reliability in estimating BM in both sexes ( p < .0001) while Macêdo's equations showed substantial reliability or males ( p < .0001) only. Mirwald and Moore's equations showed weak reliability ( p < .05 and p = .043, respectively). Conclusion: The prediction of SA using anthropometric equations was found to be reliable in categorizing individuals as late, synchronized, and/or early maturers in both sexes. However, the predictive equations of years from PHV only reliably categorized late and synchronized maturation stages in males and the synchronized maturers in females.